Near IR spectroscopy for the characterization of dispersion in polymer-clay nanocomposites - Machado, Ana Vera (2014)
© 2015 Wiley-VCH Verlag GmbH & Co. KGaA. Since their potential has become widely recognized, one of the major research lines on polymer-clay nanocomposites has focused on the preparation of well-dispersed systems. Currently, there is an understanding that a high degree of dispersion, particularly exfoliation, of the nanoclay is required to improve the overall performance. Twin screw extrusion not only allows for control of the main variables (shear, stress and time), but also, due to the typical modular construction, offers a high degree of freedom in creating the adequate screw design and enables knowledgeable alteration of the barrel. These features offer a solid basis for the development and implementation of apt in-line/on-line monitoring techniques, able to follow up the evolution of dispersion of polymer-clay nanocomposites during processing. This chapter includs the validation, implementation, and application of a methodology based on inline near-infrared (NIR) spectroscopy for the characterization of the dispersion along the extruder axis. Overall, the results obtained confirm that NIR is a valid tool for the on-line characterization of these materials, offering the possibility of assessing in real time the clay dispersion, enabling proper corrective and/or optimization actions over the material characteristics in a timely manner.